Directory of World Cinema. - Bingham, Adam (Directory of World Cinema Series., 2011)
Part of the "Directory of World Cinema" series, this title includes contributions from some of the leading academics in the field. It features film recommendations from a range of genres for those interested in watching more cinema from these regions. It also features comprehensive filmography as an index. Given the prevalence of important new wave cinemas across Eastern Central Europe in the post-war, post-Stalinist era (Poland, Hungary, Czechoslovakia, and Yugoslavia), this new volume of the "Directory of World Cinema" series charts the trends of these national cinemas. I.